Les trajectoires socio-spatiales des Franciliens depuis leur départ de chez les parents - Catherine Bonvalet; Arnaud Bringé (Temporalités)
While the analysis of residential trajectories has been a major focus of research in recent years, the influence of the social environment has rarely been taken into account. The aim of this article is to observe urban transformations via the mobility behaviors of 2.830 residents in the Paris region included in the INED “Event Histories and Contact Circle” survey (Biographies et Entourage), taking into account changes in the social structure of municipalities which are partly the result of these individual mobilities.By including social change at municipal level in the analysis of residential trajectories – i.e. taking account of the context in which they occur – several types of trajectory were identified : those which took place between municipalities with an equivalent social standing (stable or neutral trajectories, 29 %), and those which involved change, either upwards to a municipality with a higher social standing (upward trajectories, 6 %) or downwards to a municipality with lower social standing (downward trajectories, 32 %). À “nominal harmonic analysis” was also performed, to establish a typology of individuals with similar trajectory profiles.